Local Transposition and Rotation Scalp Flap for Coverage Of Scalp and Calvarial Defect : One Stage Solution - Khaled, Mohammed S.; Akhter, Farhana; Palit, Liton Kumar; Farhana, Rubaiyat; Alam, Md Saiful; Dhar, Narayan (Journal of Chittagong Medical College Teachers’ Association, 2026)
Background: Electric burn and machinery avulsion injury at scalp is very common in developing country like us. Early coverage by local flap may reduce extra cranial and also intracranial complication. To see long term functional and cosmetic outcome of local transposition/rotation scalpflap. Materials and methods: It is a prospective observational study to find out long term effect of local transposition flap over scalp/Calvarial wound.18 patients of scalp wound were included in this study with 14 male and remaining 4 were female for last 3 years (July 2022 to June 2025). Average age limit 32 years (7 years to 59 years). Patient of scalp wound actually caused by high voltage electric burn, tumour excision, bullet injury, machinery avulsion injury and road traffic accident. Five patients need intensive care unit and neurosurgical treatment for head injury. Results: All 18 patients under gone local transposition/ rotation flap for scalp wound. Only three of 18 flapshave marginal necrosis which gradually healed by dressing. Long term follows up shows complete functional and cosmetic recovery. Follow up X-ray skull shows good healing at bone and no evidence of osteomyelitis. All doner site of scalp flap covered with split thickness skin graft which remain hairless at long term follow up. Conclusion: Local subgaleal transposition/rotation scalp flap is the good option for scalp defect for variety of wound. Early coverage can prevent life threatened complication like brain abscess, CSF leakage and osteomyelitis. JCMCTA 2025 ; 36 (2) : 151-155